Cobaltoceniumethynyl gold(i) as an unusual heterodinuclear bioorganometallic fragment to study the biological properties of alkynyl gold complexes. Issue 4 (6th January 2016) - Vanicek, S.; Kopacka, H.; Wurst, K.; Vergeiner, S.; Kankowski, S.; Schur, J.; Bildstein, B.; Ott, I.
Abstract : A cobaltoceniumethynyl gold(i ) complex with a triphenylphosphane ligand triggered efficient cytotoxic effects in cancer cells in contrast to a derivative with two cobaltocenium moieties. Abstract : A cobaltoceniumethynyl gold(i ) complex with a triphenylphosphane ligand triggered efficient cytotoxic effects in cancer cells in contrast to a derivative with two cobaltocenium moieties. The complex effectively inhibited the enzyme thioredoxin reductase (TrxR) suggesting this enzyme as a possible biological target. The cellular uptake of both metal fragments of the active complex was studied by atomic absorption spectroscopy and indicated a high biological stability of the complex.